2017
DOI: 10.1021/acs.jnatprod.6b00760
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Antifungal Stilbenes Using the Enzymatic Secretome of Botrytis cinerea

Abstract: The protein secretome of Botrytis cinerea was used to perform the biotransformation of resveratrol, pterostilbene, and a mixture of both. Metabolite profiling by UHPLC-HRMS revealed the presence of compounds with unusual molecular formula, suggesting the existence of new products. To isolate these products, the reactions were scaled-up, and 21 analogues were isolated and fully characterized by NMR and HRESIMS analyses. The reaction with pterostilbene afforded five new compounds, while the reaction with a mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 62 publications
3
63
2
Order By: Relevance
“…This would explain the strong decrease in E ‐ɛ‐viniferin in the roots and the increase in vitisin B (Table ). In addition, the oxidation of stilbenes has already been reported in studies on the dimerization of monomers under the action of fungal‐derived enzymes . Furthermore, the time factor could also play a role in these differing degrees of polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would explain the strong decrease in E ‐ɛ‐viniferin in the roots and the increase in vitisin B (Table ). In addition, the oxidation of stilbenes has already been reported in studies on the dimerization of monomers under the action of fungal‐derived enzymes . Furthermore, the time factor could also play a role in these differing degrees of polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the oxidation of stilbenes has already been reported in studies on the dimerization of monomers under the action of fungalderived enzymes. 38,39 Furthermore, the time factor could also play a role in these differing degrees of polymerization. Indeed, grapevine canes that are pruned each year do not undergo much stress, whereas wood and roots that are several decades old would accumulate stilbenes over time.…”
Section: Oligomerization Of Stilbenes From Aerial To Root Partsmentioning
confidence: 99%
“…Beneveneti et al also reported the oligomerization of phenolic compounds by purified laccases of Trametes versicolor , which is a white rot fungus [ 62 ], notably the transformation of trans -resveratrol into trans -δ-viniferin. Recently, using the secretome of B. cinerea, Gindro et al have demonstrated the dimerization of trans -resveratrol into several compounds such as leachianol F/G, restrytisol B, trans / cis -δ-viniferin, and 3 β- (3′,5′-dihydroxyohenyl )-2 α -(4″-hydroxyphenyl)dihydrobenzofuran-5-carbaldehyde [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, grapes infected with this fungus can be used to produce concentrated sweet wine [14][15][16]. In addition, a recent study used the protein secretome of B. cinerea for biotransformation reactions, such as that of resveratrol [17]. Here we report the biotransformation of 4-chromanone and its analogs as a follow-up to our study using acetophenones [10] 2.…”
Section: Introductionmentioning
confidence: 94%
“…Although we used two types of phytopathogenic fungi, other studies have reported using B. cinerea and Colletotrichum spp. (species) [11][12][13]. B. cinerea can adversely affect agricultural crops as a plant pathogen.…”
Section: Introductionmentioning
confidence: 99%